Supply Chain and Distribution Analysis of Value Added of Coffee Bean in Lampung Province Indonesia - Irmayani Noer (AIBPM Publisher, 2019)
Lampung Province is one of the potential coffee producers in Indonesia, with the contribution to national exports reaching an average of 61.26 percent over the past six years. The contribution of Lampung's coffee export to national exports in 2013 was more than 70% (AEKI, 2014). However, it was interesting to explore whether this contribution also have a positive effect on added value for farmers? One aspect of justice in the supply chain can be seen from the distribution of added value among actors involved in it. Therefore a study is needed to analyze the supply chain and distribution analysis of value added of coffee beans in Lampung Province. The main performance indicators used in analyze was financial indicators for each actor involved in the coffee bean supply chain, including production costs, labor, procurement, storage, as well as margin calculation and added value. The analysis showed that the biggest added value of all actors in the coffee bean supply chain is the farmers and the smallest is the collectors. Moreover, farmers get the highest proportion of value added compared to other actors. The highest added value is obtained by farmers when they choose to sell coffee beans to the joint business group (KUB).